Materiality and Transmission of Qur’anic Exegesis in Nineteenth-Century Java - Iftitari Itsna Syayyidah; Ahmad Zaidanil Kamil; Jazilatul Atiyah Abdur Rouf (Lajnah Pentashihan Mushaf Al-Qur'an, 2026)
This study examines the codicological aspects of a manuscript of Tafsir al-Jalalayn copied by KH Sholih Tsani, a scholar within the intellectual tradition of Pondok Pesantren Qomaruddin Sampurnan Bungah Gresik. The research aims to identify the manuscript’s material characteristics, scribal patterns, paratextual elements, and the historical context surrounding its production. It employs a descriptive-analytical approach, combining direct observation of the manuscript, literature review, and interviews with local historians. The findings indicate that the manuscript was written on European paper bearing a watermark, using Naskhi script, with red ink for Qur’anic verses and black ink for the commentary. Various paratextual features such as marginal notes, reference symbols, corrections, catchwords, and a colophon are consistently present. The colophon records that the copying was completed on 14 Ramadan 1279 AH (5 March 1863 CE). This study offers a novel contribution by integrating codicological, textual, and paratextual analyses while linking the manuscript to the Haramain-Hadramaut scholarly network. In doing so, the manuscript is understood not merely as a tafsir text, but as a medium of scholarly transmission and intellectual legitimation within the pesantren tradition. Kata Kunci : Kodikologi, Manuskrip Tafsīr al-Jalālayn, KH. Sholih Tsani.